1995
DOI: 10.1518/001872095779049282
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Scheduling Systems as a Basis for the Study of Strategic Behavior

Abstract: Strategic behavior is frequently characterized by the need to decide among several courses of action, each of which may lead to a desired goal, subject to time constraints. Often strategic behavior can be regarded as a series of answers to the question, "In what sequence should I perform the set of actions required, and when should I start and stop each of them?" Scheduling theory, which is usually used to determine the sequencing of operations in such situations as transportation and manufacturing, provides n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Many studies have noted the importance of graphical representation in determining human scheduling strategies (e.g., Cegarra & Hoc, 2003;Dessouky et al, 1995;Gibson & Laios, 1978;Higgins, 1996;Sanderson, 1991). Thus, it is very important that result comprehensibility is taken into account because of the consequences it could have on schedule evaluation.…”
Section: Results Comprehensibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have noted the importance of graphical representation in determining human scheduling strategies (e.g., Cegarra & Hoc, 2003;Dessouky et al, 1995;Gibson & Laios, 1978;Higgins, 1996;Sanderson, 1991). Thus, it is very important that result comprehensibility is taken into account because of the consequences it could have on schedule evaluation.…”
Section: Results Comprehensibilitymentioning
confidence: 99%
“…For example, it is possible to distinguish between exact algorithms and approximate algorithms. However, such a classification is not really relevant from the human point of view as humans do not represent complexity in the same way as formal models (Dessouky, Moray, & Kijowski, 1995). To our knowledge, no classification of scheduling algorithms using dimensions relevant from the human point of view has been elaborated.…”
Section: Characterizing Algorithms From the Human Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Vicente (1999), interfaces should favor direct perception of visual patterns, as planners' powerful visual perception of patterns has frequently been noted (Dessouky et al, 1995;Sanderson, 1989;Trentesaux, Moray, & Tahon, 1998). Ormerod and Chronicle (1996), for instance, showed that visual perception allows planners to find close approximations to optimum solutions for simple routing problems at low computational costs.…”
Section: Decision Support and Route Selectionmentioning
confidence: 99%
“…Moray et al (1991) proposed using scheduling theory as a normative model for strategic behavior for operator tasks. Dessouky et al (1995) examine the use of classical scheduling theory to develop a conceptual framework for behavior in human-machine settings.…”
Section: Studies Of Practicementioning
confidence: 99%